SPATIAL ANALYSIS OF URBAN ECOLOGICAL CONDITION IN DENPASAR CITY, INDONESIA USING LANDSAT 9 IMAGERY - Hamim Zaky Hadibasyir; Nada Salsabila Firdaus (Purifikasi, 2022)
Denpasar City is the capital of the province of Bali where anthropogenic activities are most intensive on the island. The study of urban ecological conditions is vital for planning and monitoring the ideal condition of environmentally friendly settlements in the city of Denpasar. This research aims to 1) examine the temperature-related ecological conditions of micro-scale cities based on urban thermal field variance index (UTFVI) values and 2) assess the distribution pattern of NDVI and LST in the city of Denpasar derived from Landsat 8 satellite data. The land surface temperature (LST) and the normalized difference vegetation index (NDVI) were both derived using data from Landsat 9, which was also utilized (NDVI). Following that, UTFVI was categorized using LST. The results show that the greater the UTFVI value, the worse the state of urban ecological degradation and the greater the intensity of UHI, and vice versa. A low UTFVI value of less than 0.005 is spatially distributed throughout all districts and is characterized as an area with good to very good urban ecological quality. This category predominates in the South and East Denpasar Districts, the northern region of the North Denpasar District, and the southern region of the West Denpasar District.